Use of agile methods in software firms in the Philippines - Yang, Li (Animo Repository, 2007)
The purpose of this study is to study Agile models or practices that software firms in the Philippines have tried to adopt or adapt, and to evaluate processes and other factors affecting the successful or unsuccessful adoption or adaptation of these models or practices. This study is composed of four parts: an investigation of Agile practices in Philippine software firms, an analysis of the practices used in the U.S. and other European countries to identify the best practices, a formulation of guidelines for the adoption of Agile in Philippine software firms and an evaluation of these guidelines. In her investigation of local firms, the researcher did a preliminary survey of Philippine IT firms, and a detailed case-study of five companies found to be Agile users. The result became the basis for the formulation of the objective for each module of the program. After analyzing the practices done by American and European practitioners, the researcher came upon ten best practices, namely, refactoring, test-driven, coding standards, pair programming, continuous integration, common code ownership, daily meeting, short iteration, planning game and active stakeholder participation. Based on the above study, a series of guidelines was defined. The guidelines are for the adoption of Agile practices for Philippine software firms to elevate their quality production of software. A professional evaluation was formed on the basic criteria of guidelines, namely: correctness, completeness and clarity. The evaluation was done by three IT experts. Their valuable input became the inspiration for further study.